Determinan Kejadian Diare Pada Balita Sebuah Literatur Review - Zulaikha, Fatma; Subekti, Nina; Anjari, Laras Tri; Oktaviani, Ria; Aprilia, Via; Wahyunie, Nida (Bunda Edu-Midwifery Journal (BEMJ), 2022)
Diarrhea is one of the health problems of children in the world. One of the efforts to reduce the incidence of diarrhea in children is to identify and analyze the factors that cause diarrhea so as to minimize the incidence and mortality due to diarrhea. The purpose of this study was to analyze the risk factors for diarrhea in children. The design of this research is a literature review. The results of the analysis show that the factors that influence the incidence of diarrhea in children are vitamin A intake, exclusive breastfeeding, nutritional status, environment and immunization status.